2013
DOI: 10.1002/ejlt.201200296
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐chain alkyl esters of tyrosol and hydroxytyrosol antioxidants by cuphea oil transesterification

Abstract: Effective lipophilic antioxidants were prepared by non-aqueous enzymatic transesterification of plant phenols with cuphea oil. Tyrosol and hydroxytyrosol, abundantly available phenols from olive oil processing byproduct, were found to be predominately acylated with capric acid derived from the triglyceride fraction of the Cuphea germplasm line PSR 23 (Cuphea Viscosissima  C. lanceolata). The reaction was complete within 2 h, with a >97% conversion of either phenol using immobilized Candida antarctica lipase B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The observed differences in the FRSA could be attributed to such difference in structures of the prepared derivatives. It was stated that the efficacy of the antioxidants is also influenced by the ability of the phenolic lipids in partitioning to specific interfacial regions such as lipid‐water medium, food emulsions or in cellular matrix . The order of FRSA for the prepared compounds in the present study is as follows: 11 > α–Tocopherol ≈ 10 > 9 > BHT > 7 > 8 ≈ 6 .…”
Section: Resultsmentioning
confidence: 64%
“…The observed differences in the FRSA could be attributed to such difference in structures of the prepared derivatives. It was stated that the efficacy of the antioxidants is also influenced by the ability of the phenolic lipids in partitioning to specific interfacial regions such as lipid‐water medium, food emulsions or in cellular matrix . The order of FRSA for the prepared compounds in the present study is as follows: 11 > α–Tocopherol ≈ 10 > 9 > BHT > 7 > 8 ≈ 6 .…”
Section: Resultsmentioning
confidence: 64%
“…Various methods have been described for linking phenolic compounds to glyceridic structures . Although efficient, they often lead to complex mixtures of phenolipids, containing various isomers or compounds corresponding to different degree of phenolic grafting on the glyceridic backbone, which makes subsequent purification difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Close tendencies on the above-described antioxidant potential of HT esters were reported by other authors using distinct experimental models. Burattini et al [ 99 ] compared the previously selected three different classes of HT esters, namely with short (C2–C4), medium (C10–C12) and long (C16–C18) acyl side chains and showed that short- and medium-length chain HT esters were more effective than HT in protecting human cells (U937 and C212) from oxidative hemolysis, with HT laurate (C12) being the most effective. This derivative also exhibited better antioxidant activity than HT in the same cellular lines [ 99 ].…”
Section: Chemical Modifications Of Ole and Htmentioning
confidence: 99%
“…Burattini et al [ 99 ] compared the previously selected three different classes of HT esters, namely with short (C2–C4), medium (C10–C12) and long (C16–C18) acyl side chains and showed that short- and medium-length chain HT esters were more effective than HT in protecting human cells (U937 and C212) from oxidative hemolysis, with HT laurate (C12) being the most effective. This derivative also exhibited better antioxidant activity than HT in the same cellular lines [ 99 ]. In addition, Candiracci et al [ 100 ] found that among HT esters with fatty acids from C2 to C18, those with medium-sized acyl chains were the most effective in protecting human erythrocytes of healthy non-smoking volunteers.…”
Section: Chemical Modifications Of Ole and Htmentioning
confidence: 99%